Current food quality and safety problems in the context of ensuring food safety in Ukraine - Kotelevych, V.; Huralska, S.; Hоncharenko, V. (Scientific Progress & Innovations, 2023)
The quality, degree of harmfulness and danger of food products determine not only the health of the population, but also the genetic fund of the state, the level of development of science and industry. The priority task of modern science and practice is to limit the entry of harmful substances into the human body through food products and to highlight this problem in an informative space. The purpose of our research was to highlight the current problems of quality and safety of food products in the context of ensuring food security in Ukraine based on the results of the analysis of scientific publications. It was established that the state of the ecological situation in Ukraine has significantly worsened and the scale of environmental pollution with heavy metals, radionuclides and other harmful substances has increased several times over the last decade and is expected to continue to grow. The most "conducive" to the accumulation of heavy metals are the fodder of farm animals and milk. The silage-root type of feeding and the addition of mineral-vitamin premixes significantly reduces the transfer of Lead and Cadmium. The content of heavy metals in dairy products is 1.5 times lower than in raw milk, which indicates the influence of the technological operation on their redistribution. Out of 2,587 samples of fish and fish products examined during export-import operations of Ukraine, mercury content was exceeded in 0.12 % of samples. The mercury content in tuna muscles was at the level of 0.356‒1.889 mg/kg, which exceeded the MDR by 1.8 times. The content of mercury in the muscles of freshwater fish was in the range of 0.006‒0.315 mg/kg, which calls for increased monitoring of the content of mercury in fish, taking into account its detrimental effect on public health and its importance as an indicator of ecosystem pollution. The specific activity of 137Cs content of mushrooms and berries of forest origin, meat of wild animals and products of own production in the Polish region in most cases significantly exceeds DR- 2006, which forms large doses of internal radiation and negatively affects the health of the population. Studies conducted in 14 regions of Ukraine established an excess of nitrate content in 9. The most critical situation is in rural settlements of the Kherson region, where the excess of the average nitrate content was almost 14 GDN in farms with traditional management and almost 7 GDN ‒ in settlements with organic agriculture. Numerous scientific studies on the sanitary quality of livestock products during production and circulation require the development and organization of a microbiological risk assessment system.